Contemporary myths on boredom - Ros Velasco, Josefa (Frontiers in Sociology, 2023)
We don't know almost nothing about boredom. Even though the experience of boredom has been part of our daily life for centuries, we are far from being clear about what its suffering consists of, what its main causes and consequences are, or how we can satisfactorily escape it. This is one of the most repeated myths about boredom among some boredom scholars; one from which many others derive, causing unnecessary confusion about a phenomenon around which there exists, in fact, a whole corpus of scientific knowledge. Most of them are harmless, simple narratives from our popular culture; others, however, have the power to condition the way in which we perceive reality, to the point of becoming stigmatizing. Breaking with some of our most ingrained beliefs about boredom is not an easy task, although it is necessary to understand the true nature of this state. In my essay, I will try to disprove some of the contemporary myths that circulate about the experience of boredom. Starting with the first myth, I will explore the scope of other related myths such as those that say that the study of boredom is in its infancy, that boredom has not been given the attention it deserves, that the experience of boredom is born in modern societies, that boredom is an exclusively human condition, that boredom only happens in leisure time, that being bored is the same as doing nothing, that it is desirable to have moments of boredom, that boredom helps our brain to rest, that boredom makes us more creative, and that those who get bored is because they want to or, what is worse, that only fools get bored.